INDICATION for critical care nurses: Protocol for a quasi-experimental study testing the effects of a multi-modal education intervention for delirium care. Issue 5 (October 2021) - Ho, Mu-Hsing; (Rita) Chang, Hui-Chen; Chen, Kee-Hsin; Traynor, Victoria
Abstract: Background: Delirium is associated with serious adverse health outcomes, particularly increased intensive care unit (ICU) stay and mortality rate. Critical care nurses lack sufficient knowledge about delirium and it remains undetected and poorly managed. Aim: In this protocol, the development, implementation and evaluation of the INDICATION (INnovative DelIrium CAre educaTION) program on delirium care knowledge, confidence, competence and clinical practice among critical care nurses in Taiwan is reported. Methods: A quasi-experimental trial will be performed to examine the effects of the INDICATION program. This study will be conducted at a teaching hospital in Taiwan. Two ICUs will provide the sites to recruit critical care nurses to participate. The INDICATION program for the intervention group will be delivered as a multi-modal delirium care education intervention consisting of: (1) one face-to-face education session; (2) five online delirium care learning modules; and (3) simulation education using scenario-based objective structured clinical examination. Participants in the comparison group will only receive: (1) One face-to-face education session; and 2) five online delirium care learning modules. Outcomes including knowledge, confidence and competence of delirium care will be collected at baseline (T0), immediately after the intervention (T1), and 6 weeks postintervention (T2) to evaluate changes over time. Findings: Study protocol. Discussion: It is anticipated that the INDICATION program will improve the detection and management of delirium by critical care nurses. Conclusion: The INDICATION program highlights the importance of achieving outcomes to improve the knowledge, confidence, competence, and clinical performance of delirium care among critical care nurses.